Examining Student Motivations and Socioeconomic Realities in Kampus Merdeka Internship in Indonesia - Afra Hanifah Prasastisiwi; Qonita Luthfia Alimah; Winda Sukma Nurisa; Saffanah Calista; Ester Dwi Sabtu; Derajad Sulistyo Widhyharto (Departemen Sosiologi Universitas Gadjah Mada, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) internship program represents an effort to address the demands of modern industrialization in Indonesia. The growing need for highly educated and skilled young workers aligns with students’ aspirations to prepare for their future careers. This study aims to examine the perspectives, motivations, and socio-economic conditions of Kampus Merdeka internship participants. To achieve this, a mixed-method approach with a phenomenological perspective was employed to capture the experiences of undergraduate students across Indonesia. The study found that student interns are driven to prepare themselves for transitioning into the workforce by allocating their time and resources to work directly with partners provided by the Ministry of Education and Culture. High job competition and the need for work experience are the primary motivations for choosing Kampus Merdeka internship activities, ultimately outweighing the risks and uncertainties surrounding them, such as job insecurity, out-of-pocket expenses, opportunity costs, and high work pressure. Nevertheless, the student interns in this study managed to endure these challenges by framing the risks and uncertainties as valuable learning opportunities while pursuing professional experience. This situation reflects an illusion created by the Kampus Merdeka internship program, in which the social and economic disadvantages borne by students are obscured by the imperatives of labor market demands.